Evaluation of the Properties and Degradative Potential of Soil Isolates - Leila Iminova; Valentina Polivtseva; Tatiana Abashina; Nataliya Suzina; Inna Solyanikova (Engineering Proceedings, 2024)
Microorganisms from various taxonomic groups play a crucial role in environmental cleanup, specifically in the bioremediation of contaminated soils and aquatic ecosystems by decomposing toxic pollutants or transforming them into less toxic substrates that can be easily recycled. Over 150 cultures were examined for their capability to utilize these substances as the only source of growth in a mineral medium, with phenol concentrations in the medium varying from 0.1 g/L to 2.5 g/L, oil at 1–2%, pinoxaden and toluene up to 0.5%, and carbon tetrachloride up to 10%. It was found that the isolated bacteria belonged to the genera Rhodococcus, Pseudomonas, Peribacillus, Microbacterium, and Bacillus. As a result, strains that can efficiently eliminate various pollutants were isolated and characterized.